Checking Unsatisfiability for OCL Constraints - Clavel, Manuel; Egea, Marina; García de Dios, Miguel Angel (Electronic Communications of the EASST, 2010)
In this paper we propose a mapping from a subset of OCL into first-order logic (FOL) and use this mapping for checking the unsatisfiability of sets of OCL constraints. Although still preliminary work, we argue in this paper that our mapping is both simple, since the resulting FOL sentences closely mirror the original OCL constraints, and practical, since we can use automated reasoning tools, such as automated theorem provers and SMT solvers to automatically check the unsatisfiability of non-trivial sets of OCL constraints.